Analyzing the process of physical development of the city and presenting its appropriate strategic model, case study: Ahvaz city - ali shamai; seyed hossein vahdi nejad; soghera azarshab; Moslem Ghasemi (تحقیقات کاربردی علوم جغرافیایی)
Urbanization and urban growth as a global phenomenon have affected all the countries of the world. Ahvaz city has seen its diverse body tissues throughout its lifeless life. Over time, land use in Ahvaz city has undergone a lot of changes due to the presence of factors and forces that has been unfavorable and has affected agricultural land so much. The main objective of this research is to investigate the physical development of Ahvaz city. This research is applied in terms of nature and descriptive-analytical in terms of methodology. In order to achieve this goal, firstly, the physical expansion in the city of Ahvaz was reviewed in the comprehensive plan approved in 2010, and then 14 indicators were extracted to study the optimal development of Ahvaz city development, which were standardized using Fuzzy Logic (FUZZY) Continued for the optimal model using the ANPDEMATEL combined analysis model. Three levels for the expansion of this city have been identified in combination with OVERLAYFUZZY and GAMA/ 0 in the GIS environment, the output maps were also extracted using the ENVI and ARCGIS software. The results showed that at the level of predictive models of agricultural land with weights of 0.101 and 0.118, the most important factor has been changed in the process of physical expansion of the Ahvaz city. Also, using the map of physical expansion in the year 2010 and the outline map of the level of physical expansion in this study showed that the physical expansion of the Ahvaz city is not consistent with the comprehensive plan approved in 2010.